2005
DOI: 10.1182/blood-2004-11-4284
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of circulating human transitional B cells

Abstract: IntroductionPrimary B-cell development takes place in the bone marrow, where immature B cells must generate a functional B-cell receptor (BCR) and overcome negative selection induced by reactivity with autoantigens. [1][2][3] In mice, approximately 10% of immature B cells survive these processes and emerge from the bone marrow expressing surface immunoglobulin M (IgM) and IgD. 4 These immature "transitional" B cells transit to the spleen where they mature to become responsive to BCR-mediated signaling. [5][6][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

51
496
3
10

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 521 publications
(560 citation statements)
references
References 70 publications
51
496
3
10
Order By: Relevance
“…A similar population of B cells was also detectable in healthy individuals, albeit at a ϳ5-fold lower frequency than XLP, as well as in normal BM and cord blood (CB). The phenotype of this population resembled that of cells recently proposed to be human transitional B cells (16,17). In the current study, transitional B cells were found to display functional characteristics of immature B cells, such as the lack of expression of Bcl-2 and reduced survival, proliferation, differentiation, and chemotaxis compared with mature B cells; they also expressed unmutated Ig V region genes.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…A similar population of B cells was also detectable in healthy individuals, albeit at a ϳ5-fold lower frequency than XLP, as well as in normal BM and cord blood (CB). The phenotype of this population resembled that of cells recently proposed to be human transitional B cells (16,17). In the current study, transitional B cells were found to display functional characteristics of immature B cells, such as the lack of expression of Bcl-2 and reduced survival, proliferation, differentiation, and chemotaxis compared with mature B cells; they also expressed unmutated Ig V region genes.…”
mentioning
confidence: 63%
“…Thus, immature B cells are CD19 ϩ CD27 Ϫ CD10 ϩ IgM ϩ IgD Ϫ , while naive B cells are CD19 ϩ CD27 Ϫ IgM low IgD high , and memory B cells are CD19 ϩ CD27 ϩ and express IgM, IgG, or IgA (2,(12)(13)(14)(15). Human transitional B cells, however, remain poorly characterized, although their existence is suggested by the recent demonstration of a population of cells in peripheral blood (PB) distinguishable from mature B cells on the basis of a CD24 high CD38 high phenotype (16,17).…”
mentioning
confidence: 99%
“…It could be related to the observed overall trends of reduction of CD5 þ B cells in carriers, as all transitional B cells are CD5 positive. 18,19 The development of CD5 þ B1 B cells was severely decreased in the peritoneum of CD19-deficient mice. 20,21 Whereas human CD5 þ B cells in the blood might not be the functional equivalence of mouse B1 B cells, they were equally affected in CD19-deficient mice and patients with CD19 homozygous mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike switched memory B cells, IgM memory B cells do not promote long-term protective humoral immune responses and it has been proposed that this B cell subset be regarded as natural effector B cells which bridge innate and adaptive immune responses (15). The ontogeny of IgM memory B cells in humans remains unclear; one suggestion is that this B cell subset may be derived from transitional B cells which are a naive B cell population that need the spleen to complete their development to mature B cells (19,20). Increased numbers of transitional B cells are a characteristic feature of several inherited humoral immunodeficiency conditions and HIV infection (21,22) and are associated with decreased memory B cells (21).…”
Section: Loss Of Discretementioning
confidence: 99%